1998
DOI: 10.1007/bf03348039
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combined treatments in NIDDM patients with secondary failure to sulphonylureas. Is it predictable?

Abstract: The treatment of NIDDM patients with secondary failure to sulphonylurea is a common problem. We performed a crossover study in 50 NIDDM patients with secondary failure to glibenclamide by comparing the addition to sulphonylurea of either a low-dose bedtime NPH insulin or a t.i.d. oral metformin and by analyzing treatment efficacy in relation to patient and disease characteristics. Both combined therapies clearly improved glycaemic control. HbA1 c were similarly reduced by the addition of either bedtime NPH ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 13 publications
4
6
0
Order By: Relevance
“…These findings further suggest that the SERCA pump in the heart is a major regulator of not only cardiac but whole body glucose homeostasis, consistent with recent studies in liver tissue which also demonstrated that SERCA2b overexpression in the liver of obese mice lowered blood glucose concentration and improved glucose tolerance [41,42]. Taken together, these results suggest that activation of novel insulin-independent pathways regulating glucose transport could provide a much needed alternate therapeutic target for diabetic patients, for many of whom proper control of hyperglycemia by insulin-sensitizing therapy is lacking [43,44]. Since SERCA pump dysfunction contributes to the pathogenesis of diabetic cardiomyopathy, a common and insidious complication, overexpression of the SERCA pump is a promising gene therapy approach for the diabetic population [5,17,45].…”
Section: Discussionsupporting
confidence: 81%
“…These findings further suggest that the SERCA pump in the heart is a major regulator of not only cardiac but whole body glucose homeostasis, consistent with recent studies in liver tissue which also demonstrated that SERCA2b overexpression in the liver of obese mice lowered blood glucose concentration and improved glucose tolerance [41,42]. Taken together, these results suggest that activation of novel insulin-independent pathways regulating glucose transport could provide a much needed alternate therapeutic target for diabetic patients, for many of whom proper control of hyperglycemia by insulin-sensitizing therapy is lacking [43,44]. Since SERCA pump dysfunction contributes to the pathogenesis of diabetic cardiomyopathy, a common and insidious complication, overexpression of the SERCA pump is a promising gene therapy approach for the diabetic population [5,17,45].…”
Section: Discussionsupporting
confidence: 81%
“…There is evidence that more insulin-resistant patients with higher Cpeptide values have increased response to thiazolidinediones [105][106][107][108]. This does not appear to be the case for metformin, sulphonylureas and dipeptidyl peptidase-4 (DPP-4) inhibitors [84,105,[109][110][111].…”
Section: Treatment Change In Non-insulin-treated Patientsmentioning
confidence: 99%
“…Higher MMTT stimulated c-peptide has been shown to be present in patients who respond to metformin and glibenclamide in combination but GST c-peptide did not predict response to glibenclamide alone [42, 43]. High fCP is associated with response to the thiazolidinediones, rosiglitazone and pioglitazone, which is in keeping with their action of reducing insulin resistance [44, 45].…”
Section: Prediction Of Response To Non-insulin Therapies In T2dmmentioning
confidence: 99%